Experience of Implementing Trilanguage in Kazakhstan on the Example of Pedagogical Universities - S.D, Abisheva; M.M, Khavaidarova; D.A, Sabirova; ., Ongarbaeva A; Madina, Abaeva (Journal of Ecohumanism, 2024)
The article is devoted to the experience of introducing trilingualism in Kazakhstan using the example of pedagogical specialties. The article identifies the main problems necessary for the successful implementation of trilingualism. Along with this, trends and prospects are identified. The article examines in detail the history of teaching methods of Kazakh, Russian, English and indirect works on language learning and works of domestic scientists on methodology. Issues in teaching two or more languages